Addressing Risky Sexual Conduct Among Out-of-School Adolescents in Ibadan, Nigeria: An Intervention Framework Targeting Fatalistic Beliefs and Early Sexual Debut - Adewuyi, Habeeb Omoponle; Ganiyu , Oluwaseyi Quadri (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: To combat the public health threat of risky sexual behavior, this initiative targets out-of-school adolescents in Ibadan. It leverages research findings to create targeted interventions addressing key predictors like Fatalistic Belief and early sexual initiation, aiming to reduce risks and strengthen coping skills. Purpose of the Study: This study examined the influence of Fatalistic Belief, Age of Sexual Initiation and Religiousity on risky sexual conduct among sexually active Out-of-school adolescents in Ibadan. Methods: A multistage sampling process and a descriptive survey of correlational design were used. Out-of-school adolescents (N = 287; 52.61% female, 47.39% male) aged 11 to 19 years old (M = 16.07, SD = 4.57) took part in the study. Participants completed self-report measures, including the Fatalistic Belief Questionnaire (α = 0.79), the General Religiosity Scale (α = 0.87), and the Sexual Risk Behaviour Scale (α = 0.81). Results: The results indicated a significant and positive link between the age of sexual initiation and risky sexual behaviour among teenagers who engaged in sexual activity outside of school. (r = .570; p.<05), Fatalistic Belief (r = .593; p.<05), and Religiousity (r = .378; p.<05); the multiple correlation coefficient of (R = 0.704, p<.05) and multiple regression adjusted coefficient (R2 = 0.490). Fatalistic Belief (β = .422; t = 9.122; p<0.05) made the most significant contribution, followed by Age of Sexual Initiation (β = .353; t = 7.133; p<0.05) and Religiousity (β = .116; t = 2.453; p<0.05). According to the study's findings, efforts should be made to curb risky sexual behaviour and address young people's capacity to handle romantic pressure, which is a defining characteristic of this developmental stage.